Do blood components affect the production of reactive oxygen species (ROS) by equine synovial cells in vitro? - Patrícia M. Brossi; Raquel Y.A. Baccarin; Cristina O. Massoco (Pesquisa Veterinária Brasileira, 2012)
Blood-derived products are commonly administered to horses and humans to treat many musculoskeletal diseases, due to their potential antioxidant and anti-inflammatory effects. Nevertheless, antioxidant effects have never been shown upon horse synovial fluid cells in vitro. If proved, this could give a new perspective to justify the clinical application of blood-derived products. The aim of the present study was to investigate the antioxidant effects of two blood-derived products - plasma (unconditioned blood product - UBP) and a commercial blood preparation (conditioned blood product - CBP)¹ - upon stimulated equine synovial fluid cells. Healthy tarsocrural joints (60) were tapped to obtain synovial fluid cells; these cells were pooled, processed, stimulated with lipopolysaccharide (LPS) or phorbol 12-myristate 13-acetate (PMA), and evaluated by flow cytometry for the production of reactive oxygen species (ROS). Upon addition of any blood-derived product here used - UBP and CBP - there was a significant decrease in the oxidative burst of synovial fluid cells (P<0.05). There was no difference between UBP and CBP effects. In conclusion, treatment of stimulated equine synovial cells with either UBP or CBP efficiently restored their redox equilibrium.